Outcomes of Complex Gastroschisis - Ilhama, Jafarli; Alexandra, Richards; Allahverdi, Musayev; Nigar, Allahverdiyeva; Ines, Castro-Moore; Homero, Brum; Morcos, Gobriel; Heydar, Mammadli; Turan, Mammadli (Journal of Neonatal Surgery, 2025)
Background Gastroschisis, an anterior abdominal wall defect, is associated with significant morbidity and mortality. This study aims to evaluate the early outcomes of neonates with complex gastroschisis and correlate outcomes with prevalent types of complications, such as a line infection and NEC. Methods A retrospective review was performed at multiple pediatric surgical centers (January 2001 and December 2019). Statistical analysis of categorical variables between the cohorts of the primary closure versus silo placement was conducted and 95% confidence intervals (CI) for variables were calculated. Results Two hundred and thirty-four neonates with gastroschisis were identified. The cohort of neonates having undergone silo closure had a longer duration of total parenteral nutrition (TPN) (32.5 vs. 48.17; P = .006), prolonged hospitalization (40.18 vs. 54.15; P = .007) and higher incidence of concomitant of bowel atresia (0.12 vs.0.20; P= .004). There was no difference observed in survival. Multivariate logistic regression demonstrated that time to closure and number of surgeries were significantly related to LOS as an independent variable. Conclusion The time to silo closure is the most significant variable related to the duration of TPN and hospitalization in gastroschisis patients, determined by the number of surgeries and severity of the disease. Furthermore, NEC and line infection were high after primary closure.